Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18203/2394-6040.ijcmph20181252
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of prevalence of internet addiction and its association with mental health among college going students in Nagpur city

Abstract: Background: The Internet has become an integral part of life. India is the third largest country in the world next to china and United States in respect of the number of internet users. Adolescents usually have poorer self- control, worse self-regulation, and poorer cognition as compared to adults and are considered the most vulnerable group to the temptations of the internet. Objective of the study was to understand the patterns, preferred use of internet, prevalence Internet addiction and its effect on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…The current study participants were principally mild to moderate internet users were quite similar with multiple Indian studies [53,54]. These study participants mainly use the internet for entertainment, internet gaming, social networking, online communication, and academic reasons which were also like earlier overseas studies [55][56][57][58].…”
Section: Discussionsupporting
confidence: 66%
“…The current study participants were principally mild to moderate internet users were quite similar with multiple Indian studies [53,54]. These study participants mainly use the internet for entertainment, internet gaming, social networking, online communication, and academic reasons which were also like earlier overseas studies [55][56][57][58].…”
Section: Discussionsupporting
confidence: 66%
“…Bagday et al study in Nagpur city showed 5.96% were using internet on mobile phones for chatting, 59.59% for shopping and 40.92% for games was less compared to our study. 25 Mobile phone was used by 14.4%, 5.8% for playing games and for watching movies and listening songs it was 21.81%, 8.3% according to Damor et al and Ghosh et al which was again less compared to our study. 22,23 A study conducted by Damor et al in Gujarat showed that 41.8% students said mobile phones hampered their academic performance which is almost similar to our study.…”
Section: Discussioncontrasting
confidence: 60%
“…Bagday et al study in Nagpur city showed 5.96% were using internet on mobile phones for chatting, 59.59% for shopping and 40.92% for games was less compared to our study. 3 For playing games, mobile phone was used by 14.4%, 5.8% and for watching movies and songs 21.81%, 8.3% according to Damor et al and Ghosh et al was again less compared to our study. 4,10 A study conducted by Damor et al in Gujarat indicated that 41.8% said mobile phones impaired academic performance which is almost similar to our study.…”
Section: Discussionmentioning
confidence: 46%